Tribological properties of hydroxyapatite-coated nanorods on Ti-6Al-4V surfaces - Sarah Akua Osafo; Tabiri Asumadu; Desmond Klenam; Precious Etinosa; John David Obayemi; Benjamin Agyei-Tuffour; Abu Yaya; David Dodoo-Arhin; Stanley Chijioke Eluu; Wole Soboyejo (Scientific Reports)
Abstract This paper presents the tribological properties and bioactivity of nanostructured hydroxyapatite (HA) from biowaste sources and coated onto Ti-6Al-4V substrates using a novel pack cementation method. The process introduced HA pillars/nanorods on the surfaces of Ti-6Al-4V to enhance their osseointegration for dental implants. The mechanical and tribological properties were studied with nanoindentation, and pin-on-disk techniques, following the microstructural characterization of the coatings with atomic force microscopy, X-ray diffraction, Raman spectroscopy, scanning electron microscopy, and energy dispersive x-ray spectroscopy. The study also examines the surface bioactivity and elucidates the underlying friction and wear mechanisms of the HA-coated and annealed Ti-6Al-4V surface. The study results show a bone bonding capacity of the biowaste-derived HA-coated substrate with improved hardness and tribological properties. The implications of the study are discussed for the development of nano-structured HA-coated Ti-6Al-4V for dental implants with improved osseointegration for dental and biomedical applications.